Pension reform in Slovakia : the context of economic globalisation - Lesay, Ivan (Brussels, 2006)
This paper presents an analysis of the pension system reform in Slovakia. The context of economic globalisation is crucial in any assessment of this topic. The paper is organised in six sections. The basic features of the pension system before and after the reform are surveyed briefly in section 2. The paper describes the legislative and institutional basis of the two systems, their respective components and the ways of disbursing pensions in each system. Sections 3, 4 and 5 constitute the paper's core. Section 3 lists the reasons for reform, categorising them in terms of stated and real reasons. As regards the former, it seeks to interpret and question the usually presented grounds, especially the unsustainability of the previous way of financing the pension system. The paper then looks at the real grounds for reform: particular attention is paid to ideological and political grounds, the influence of the international financial institutions and institutional investors' efforts to expand the financial markets. Section 4 characterises the risks and possible social impact of reform; in particular, it analyses the risk of uncertainty, but also the problem of rates of return in the reformed system. Section 5 seeks to define criteria of public interest in relation to the pension system and also evaluates pay-as-you-go and prefunded schemes on this basis. Section 6 briefly outlines measures that might help to protect the pension system from various threats. The final section looks at pension reforms in Central and Eastern Europe in order to present an example of welfare state retrenchment trends in the post-Communist region.